Klyanemsya mstit' gitlerovskim zakhvatchikam! - Zhukov, Nikolay; Klimashin, Viktor (Изобразительное искусство, 1943)
Elderly man in Red Army uniform and younger men in uniform, both raising weapons in salute Original title: Клянемся мстить гитлеровским захватчикам! PO-1027